THE INFLUENCE OF ECONOMIC GROWTH, PROVINCIAL MINIMUM WAGE, OPEN UNEMPLOYMENT RATE AND EDUCATION ON POVERTY IN LAMPUNG PROVINCE IN 2010-2023 FROM THE PERSPECTIVE OF MASLAHAH MAQASHID AL-SYARIAH - Lestari, Elza Dwi; Muhammad Yusuf Bahtiar; Is Susanto (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the influence of economic growth, provincial minimum wage, open unemployment rate, and education on poverty in Lampung Province in the 2010-2023 period from the perspective of the benefit of murlah. Stable economic growth is expected to improve people's welfare, while the UMP is designed to provide protection for workers' purchasing power. The open unemployment rate reflects challenges in providing employment opportunities, which have the potential to increase poverty rates if not addressed properly. Education plays an important role in reducing poverty through increasing skills, productivity and employment opportunities. This research uses a quantitative approach with secondary data using an approach using Vecm model analysis. Vecm model analysis or (Vector Error Correction model) is a model derived from Var. The assumptions that need to be met are the same as Var, except for the problem of stationarity to explore the relationship of these variables to poverty, as well as analyzing their relevance based on the principles of maslahat murlah which aims to create general prosperity in the context of sharia. Short-term research results show that only the economic growth variable has a positive effect on poverty in Lampung Province. In the long term, the provincial minimum wage variable has a negative effect on poverty in Lampung Province, while economic growth, the open unemployment rate and education have no effect on poverty in Lampung Province.